The sands of medium density and sandy loam density differences investigation while cement injection and pressuremetry crimping - Ihnatov, Siergey (Budownictwo i Architektura / Civil and Architectural Engineering, 2022)
The article focuses on the study of medium density sand and sandy loam density changes during water-cement solute injection and pressiometer expansion. Cement mortar injection is performed into boreholes under small pressure of up to 300 KPa resulting in radial well expansion. This expansion process also takes place during pressiometer studies. A cavity of compacted soil is formed around the expended boreholes in radial direction; the anchor and pile load determine field studies of the load, which they can perceive along lateral surface. It is worth noting that they frequently do not coincide with the calculated values. Following field anchor excavations, it was observed that root shearing can occur both directly at the contact between the cement root and the soil and at some distance from it. Subsequent laboratory studies revealed that when the soil is pressed, its density can change along a sinusoid, comprising pressed zones and decompaction zones. This gives rise to the displacement of the shear zone at the contact between the root and the soil.